Evaluasi Kinerja Termal Sistem HVAC Tipe Split duct Menggunakan Refrigeran R-410A pada Bangunan Dua Lantai - Rizqi Ardiansyah; Gunawan Hidayat; Riki Effendi (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Experimental evaluation of the thermalperformance of the split duct type Heating,Ventilation, and Air Conditioning (HVAC) systembased on R-410A refrigerant in a two-story building ina tropical climate. The main focus of the research isdirected at the characteristics of temperaturedistribution, heat transfer capacity, performancecoefficient (Coefficient of Performance - COP), aswell as thermal efficiency of the Carnot cycle. Testingwas carried out for four weeks in real operatingconditions with direct measurements at the diffuserpoints to obtain parameters of temperature, pressure,and compressor power. The experimental results showthat the temperature of the compressor and condenserincreases proportionally to the cooling load, while thetemperature of the evaporator is stable in the range of255-275 K. The COPactual value ranges between 2.8-3.5, with a system efficiency of 50-85% compared toideal conditions. The higher performance on thesecond floor emphasizes the influence of the verticalthermal load on the actual cooling capacity. Overall,the split duct system based on R-410A shows goodoperational stability and energy efficiency, making itsuitable for cooling applications in low-rise buildingsin tropical climates.